2015
DOI: 10.1016/j.bbamcr.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

An optical labeling-based proliferation assay system reveals the paracrine effect of interleukin-6 in breast cancer

Abstract: Proliferation analysis is one of the basic approaches to characterize various cell types. In conventional cell proliferation assays, the same sample cannot be observed over time, nor can a specific group within a heterogeneous population of cells, for example, cancerous cells, be analyzed separately. To overcome these limitations, we established an optical labeling-based proliferation assay system with the Kaede protein, whose fluorescence can be irreversibly photoconverted from green to red by irradiation. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Once in the CNS, AQP4-IgG causes astrocyte cytotoxicity, initially by complement activation and then by a cascade of inflammatory events such as granulocyte infiltration and then macrophage infiltration, then causes further disruption of the blood-brain barrier, oligodendrocyte death, and ultimately neuronal cell death [27]. Moreover, tumor altered immune status by secreting cytokines, such as interleukin 6 [28], leading to patients more susceptible to immune attack.…”
Section: E P T E Dmentioning
confidence: 99%
“…Once in the CNS, AQP4-IgG causes astrocyte cytotoxicity, initially by complement activation and then by a cascade of inflammatory events such as granulocyte infiltration and then macrophage infiltration, then causes further disruption of the blood-brain barrier, oligodendrocyte death, and ultimately neuronal cell death [27]. Moreover, tumor altered immune status by secreting cytokines, such as interleukin 6 [28], leading to patients more susceptible to immune attack.…”
Section: E P T E Dmentioning
confidence: 99%
“…Signifi cant elevation of serum IL-6 is found in breast cancer patients when compared with healthy controls [55,56]. Breast cancer cells may secrete IL-6 to support the proliferation of cancer, and reduction of proliferation of cancer is observed after IL-6 knockdown [57]. In another study about breast cancer, the expression of IL-6 is associated with the expression of estrogen receptor [58].…”
Section: The Rationale Of Developing Anti-il-6 For the Clinical Theramentioning
confidence: 95%
“…Our results showed that NKX6.1 controls tumor formation and cell growth. The knockdown system [22,23]. The qRT-PCR analysis showed that NKX6.1 expression was increased as a result of IL-6 knockdown (Fig.…”
Section: A Negative Feedback Loop In the Nkx61 -Il-6 Networkmentioning
confidence: 99%
“…We searched genes involving cell proliferation based on gene ontology, and obtained candidate genes ( Supplementary Table S4). Among these candidates, this study focused on IL6, the gene encoding the IL-6 protein, because secretion of IL-6 is high in basal-like breast cancer, where it exhibits a paracrine effect to positively regulate cell growth [22,23,28]. We measured IL6 mRNA levels in NKX6.1 knockdown and knockout cells by qRT-PCR.…”
Section: Nkx61 Up-regulates Il6 Expression In Basal-like Breast Cancmentioning
confidence: 99%
See 1 more Smart Citation